Academic workloads: what does a manager need to consider?. Issue 6 (2nd November 2022) - Crisp, Beth R.
ABSTRACT: Utilising Bacchi's framework 'What's the problem represented to be?' the literature on managing academic workloads was analysed to explore why workload allocation models are deemed essential in the contemporary university and the assumptions which underpin workload allocations. Whether due to the need for efficient use of scarce resources or ensuring equity for staff, workload allocation models are promoted as an accurate measure of each individual's workload and as a measure of accountability. The literature privileges the views of staff whose workloads are 'managed' but unable to do their work within their contracted hours. Universities justify long hours of unpaid overtime as a norm of professionalism. Critical issues for managers are identified, and suggestions to enable them to be more effective in the process of workload allocation are presented.